2020
DOI: 10.1017/s026646741900035x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity metrics of spider communities associated with an understorey plant in tropical rain forest fragments

Abstract: Human activities change the biodiversity of ecological communities in at least three dimensions: ecologically, taxonomically and functionally. Gathering information on these three dimensions allows the improvement of biodiversity assessments and the increased understanding of anthropogenic impact on natural communities. In this study, we analysed the spider community associated with the tropical plant Heliconia aurantiaca in two contrasting habitat types: continuous forest and forest fragments in south-eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Their predatory function and efficacy in pest control is particularly high in the tropics (Michalko et al, 2019). However, rainforest conversion may threaten these services, as re-colonization of disturbed areas likely depends on natural rainforest as a source of high spider richness (Benítez-Malvido, Martínez-Falcón & Durán-Barrón, 2020;Floren & Deeleman-Reinhold, 2005). Recently, it has been demonstrated that the complexity of ground-spider communities decreases following rainforest conversion to rubber and oil palm plantations (Potapov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their predatory function and efficacy in pest control is particularly high in the tropics (Michalko et al, 2019). However, rainforest conversion may threaten these services, as re-colonization of disturbed areas likely depends on natural rainforest as a source of high spider richness (Benítez-Malvido, Martínez-Falcón & Durán-Barrón, 2020;Floren & Deeleman-Reinhold, 2005). Recently, it has been demonstrated that the complexity of ground-spider communities decreases following rainforest conversion to rubber and oil palm plantations (Potapov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the structure of the vegetation is expected to influence the diversity of spiders found in the coffee plantation. Many other studies have also demonstrated that there exists a definite correlation between structural complexity of habitat and spider species diversity (Uetz 1979;Rosenzweig 1995;Rendon et al 2006;Rodriguez et al 2015;Malvido et al 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, vegetation architecture plays an important role in spider composition in structurally complicated habitats and vegetations, with the ability to sustain a higher spider abundance and diversity. Consequently, enhancing understory vegetation complexity in oil palm plantations potentially increases spider abundance and diversity (Stokmane and Spungis 2016;Ashton-Butt et al 2018;Spear et al 2018;Romero et al 2019;Benitez-Malvido et al 2020;Hood et al 2020;Luke et al 2020;Pashkevich et al 2020).…”
Section: Discussionmentioning
confidence: 99%